(3QSGdI GdeSM Ydi GdNa GdPi JMJg LhQH Gh ZjQJ GdLhN GdJNjfs - (3eMjj GdOjf GdafGQjs
(3ChdgG (B:s
(3GdMeO ddg GdPi Naa GdJcGdja GdTGbI Yf YHGOg GdeDefjf CeG HYO aEf YdeGA GdCeI bHd gPG GdReGf cGfhG jaJhf Edi gPG GdBf HLhGR GdeSM Ydi GdNa s
(3BNQgG (B:s
(3bGd GdTjN GdLhQLGfi bdJ deMeO Hf GdMSf QCjJ QLdkG JhVC heSM Ydi Najg fMeO Gddg JYGdi ai GdChd hGdBNQ ef GdcdGe s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI (B21s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9237) s
Keywords: (3CUhd Gdabgs